Avaliação, identificação e atividade enzimática de bactérias psicotróficas presentes no leite cru refrigerado - Silva, Priscilla Diniz Lima da (2005)
Extended storage of refrigerated milk can lead to reduced quality of raw and processed milk, which is a consequence of the growth and metabolic activities of psychrotrophic bacteria, able to grow under 7oC or lower temperatures. Although most of these microorganisms are destroyed by heat treatment, some have the potential to produce termoresistant proteolytic and lipolytic enzymes that can survive even UHT processing and reduce the processed products quality. Recently, the IN 51 determineds that milk should be refrigerated and stored at the farm what increased the importance of this group of microorganisms. In this work, psychrotrophic bacteria were isolated from 20 communitarian bulk tanks and 23 individual bulk tanks from dairy farms located at Zona da Mata region of Minas Gerais State and from southeastern Rio de Janeiro. Selected milk dilutions were plated on standard agar and after incubation for 10 days at 7oC, five colonies were isolated, firstly using nutrient agar and after using McConkey agar for 24 hours at 21oC. The isolates were identified by morphology, Gram stain method, catalase production, fermentative/oxidative metabolism and by API 20E, API 20NE, API Staph, API Coryne or API 50 CH (BioMerieux). In order to ensure reproductibility, API was repeated for 50% of the isolates. Species identification was considered when APILAB indexes reached 75% or higher. 309 strains were isolated, 250 Gram negative and 59 Gram positive. 250 Gram negative isolates were identified as: Acinetobacter spp. (39), Aeromonas spp. (07), A. Hydrophila (16), A. sobria (1), A. caviae (1), Alcaligenes feacalis (1), Burkholderia cepacia (12), Chryseomonas luteola (3), Enterobacter sp. (1), Ewingella americana(6), Hafnia alvei (7), Klebsiella sp. (1), Klebsiella oxytoca (10), Yersinia spp. (2), Methylobacterium mesophilicum (1), Moraxella spp. (4), Pantoea spp. (16), Pasteurella sp. (1), Pseudomonas spp. (10), P. fluorescens (94), P. putida (3), Serratia spp. (3), Sphigomonas paucomobilis (1). Five isolates kept unidentified. Pseudomonas was the predominant bacteria found (43%) and P. fluorescens the predominant species (37.6%), in accordance with previous reports. Qualitative analysis of proteolytic and lipolytic activity was based on halo formation using caseinate agar and tributirina agar during 72 hours at 21oC and during 10 days at 4°C, 10oC and 7°C. Among 250 Gram negative bacteria found, 104 were identified as Pseudomonas spp. and 60,57% of this group showed proteolytic and lipolytic acitivities over all four studied temperatures. 20% of Acinetobacter, Aeromonas, Alcaligenes, Burkholderia, Chryseomonas, Methylobacterium, Moraxella presented only lipolytic activity. Some isolates presented enzymatic activity in one or more studied temperatures. Among Gram positive bacteria, 30.51% were proteolytic and lipolytic at 10oC, 8.47% were proteolytic at 7oC, 10oC, and 21oC, 8.47% were proteolytic at all studied temperatures (4oC, 7oC, 10oC and 21oC) and 3.38% were proteolytic only at 21oC. At 4oC, only one isolate showed proteolytic activity and six isolates were lipolytic. In relation to Gram negative microorganisms, 4% were proteolytic and lipolytic at 7oC, 10oC and 21oC, 10% were proteolytic at 10oC and 4.4% were lipolytic at 4oC, 7oC, 10oC and 21oC, while 6.4% of all isolates were proteolytic and lipolytic at 10oC and 21oC as well as lipolytic at 4oC and 7oC. These findings are in accordance with previous researches that pointed out Pseudomonas as the predominant psycrotrophic flora in stored refrigerated raw milk